KERUKUNAN UMAT BERAGAMA DALAM PERSPEKTIF ISLAM - Juandi Juandi (Akademika : Jurnal Pemikiran Islam, 2013)
Persoalan mendasar dalam kerukunan umat beragama adalah ketidaksamaan pandangan dalam memahami keyakinan agama lain. Tolak ukur kebenaran agama “orang lain” didasari pada agama kita bukan agama “orang lain” itu sendiri. Islam, dalam pengertian yang sesungguhnya, memberi peluang keselamatan bagi keyakinan lain, sehingga kerukunan beragama bisa direalisasikan. Namun, dalam pengertian khusus, Islam hanya membuka peluang dialog pada level sosial, tidak dalam level ritual. Dengan demikian, peluang menjalin kerukunan umat beragama dalam Islam masih sangat mungkin dilakukan.One of the fundamental issues in religious harmony is inequality in view of understanding the beliefs of other religions. These benchmarks religious truth "others" based on our religion is not a religion "others" itself. Islam, in a real sense, provide an opportunity for the safety of other faiths, so that religious harmony can be realized. However, in a special sense, Islam is only open opportunities of social dialogue at the level, not the level of ritual. Thus, the opportunity to establish religious harmony in Islam is still very possible